Feature-based face recognition system using utilized artificial neural network - Chai, Tong Yuen (School of Mechatronics Engineering, 2009)
This project aims to reduce the effect of critical conditions such as excessive illumination, facial expressions, hairstyles, beard and moustache which have affected the performance of face recognition since ages ago.